Pendidikan Karakter Bersahabat Dan Komunikatif Melalui Kegiatan Osis di MAN 3 Agam Plus Keterampilan Kubang Putiah - Syawal Muslianti; Yulia Rahman; Khairuddin Khairuddin; Bambang Trisno (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research is motivated by the fact that there are still OSIS members who are engrossed in social media, there are still OSIS members who are not able to communicate well when asked to appear, there are still OSIS members who lack the courage to express their opinions in front of the forum, there are still OSIS members who are not lacking in courage, appreciate, for example, whwn friends have on opinion, there are still OSIS members who don’t care, for example when a friend is in trouble, there are still OSIS members who are negligent in their duties, there are still OSIS members who are less active in, for example, asking questions and it is difficult for OSIS members to apply a friendly charakter. and communicative, and so on. The purpose of this research is to find out the OSIS activities, find out the friendly and communicative character education contailed in the OSIS activities and to find out the impact of OSIS activities on friendly and communicative charakter. The type of research used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The data analysis techniques used are data reducation, data display, and data verification. Result of research at MAN 3 Agam: OSIS routine gate picket activities, cleaning prayer rooms, scheduling calls to prayer and prayers, muhadharah and meetings. Non-routine activities MAN Competition, Classmeeting, LDK, class XII farewell, HBN, HBI. LDK OSIS activitie, muhadharah, meetings, MAN Competition, Classmeeting, teacher’s day, class XII farewell can educate friendly and communicative charakter. The impact of this OSIS activitiy is that OSIS administrators can communicate politely, be good listeners, be attentive, cooperate, be respectful and be active.